Meningkatkan Perekonomiaan Masyarakat Melalui Media Sosial - Rajiman; Juniardi; Hery Riyanto; Susilowati; I Ketut Aditya; Kadek Semaredane (CV. Multi Kreasi Media, 2022)
The development of information technology brings a change in society. Social media is a technological sophistication-based media classified from various forms, such as magazines, internet forums, weblogs, social blogs, microblogging, wikis, broadcasts, photos or images, videos, ratings and social bookmarking. Social media has several impacts on life, namely positive impacts and negative impacts. This community service activity was carried out on June 15, 2021 and is located in the Selaki Beach Tataan Building Village. The method in this research is descriptive qualitative. The purpose of this community service activity is to improve the community's economy through social media, introduce tourist attractions, and introduce handicrafts in the Selaki Beach Tataan Building Village. This study concluded that in the coastal area, Selaki requires a cellphone or still has limited signal and only certain sim cards can still be accessed, while those who have children only have sophisticated cellphones to attend online schools.